2006
DOI: 10.1083/jcb.200606016
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 8 functions as a negative regulator of neurite outgrowth and inducer of neuronal apoptosis

Abstract: Toll receptors in Drosophila melanogaster function in morphogenesis and host defense. Mammalian orthologues of Toll, the Toll-like receptors (TLRs), have been studied extensively for their essential functions in controlling innate and adaptive immune responses. We report that TLR8 is dynamically expressed during mouse brain development and localizes to neurons and axons. Agonist stimulation of TLR8 in cultured cortical neurons causes inhibition of neurite outgrowth and induces apoptosis in a dissociable manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
243
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 244 publications
(259 citation statements)
references
References 20 publications
12
243
1
3
Order By: Relevance
“…In Ma's study, they applied 500 μmol/L loxoribine to cultured neurons and did not detect a negative effect on neurite outgrowth [31] . We used 1 mmol/L loxoribine and did find a reduction of dendritic length [11] .…”
Section: Tlrs and Neuronal Morphogenesismentioning
confidence: 96%
See 4 more Smart Citations
“…In Ma's study, they applied 500 μmol/L loxoribine to cultured neurons and did not detect a negative effect on neurite outgrowth [31] . We used 1 mmol/L loxoribine and did find a reduction of dendritic length [11] .…”
Section: Tlrs and Neuronal Morphogenesismentioning
confidence: 96%
“…Thus, they concluded that the negative effect of R848 is mediated via TLR8 but not TLR7 [31] . However, their results are in conflict to many recent studies from various laboratories regarding the expression of TLR7 in neurons [10,11,20,32] , as evidenced by the results of in situ hybridization, quantitative polymerase chain reaction (Q-PCR), and immunostaining using TLR7 antibodies [10,11,20,32] .…”
Section: Tlrs and Neuronal Morphogenesismentioning
confidence: 98%
See 3 more Smart Citations